2011
DOI: 10.1021/la1048369
|View full text |Cite
|
Sign up to set email alerts
|

Hemocompatibility of Poly(vinylidene fluoride) Membrane Grafted with Network-Like and Brush-Like Antifouling Layer Controlled via Plasma-Induced Surface PEGylation

Abstract: In this work, the hemocompatibility of PEGylated poly(vinylidene fluoride) (PVDF) microporous membranes with varying grafting coverage and structures via plasma-induced surface PEGylation was studied. Network-like and brush-like PEGylated layers on PVDF membrane surfaces were achieved by low-pressure and atmospheric plasma treatment. The chemical composition, physical morphology, grafting structure, surface hydrophilicity, and hydration capability of prepared membranes were determined to illustrate the correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 31 publications
2
89
0
Order By: Relevance
“…Though, the estimation of protein adsorption on the membrane surfaces should be considered not only with respect to surface hydrophilicity but also with respect to the hydration capacity of the membranes [31]. It is reported that the formation of the bound water layer on a surface is considered crucial to repel protein and generate anti-biofouling surface 11.…”
Section: Membrane Hydration and Bsa Adsorption Studiesmentioning
confidence: 99%
“…Though, the estimation of protein adsorption on the membrane surfaces should be considered not only with respect to surface hydrophilicity but also with respect to the hydration capacity of the membranes [31]. It is reported that the formation of the bound water layer on a surface is considered crucial to repel protein and generate anti-biofouling surface 11.…”
Section: Membrane Hydration and Bsa Adsorption Studiesmentioning
confidence: 99%
“…Many previous studies have shown that an effective mean to reduce membrane fouling was first to increase the surface hydrophilicity of membranes, the hydrophilic moieties preventing nonspecific adsorption of proteins to occur by reducing the hydrophobic interactions between the proteins and the hydrophobic surface [11,40]. But especially when a porous media is considered rather than a dense membrane, surface hydrophilicity is not enough since some bio-fouling agents can still penetrate within the pores and interact with the polymer inside the porous structure.…”
Section: Surface Hydrophilicity Of the Pegylated Pvdf Membranesmentioning
confidence: 99%
“…Although the biofouling resistance of PEGylated PVDF membrane surfaces with varying grafting coverage of PEG brushes via the grafting from or grafting onto approach has been studied [10,11], the scientific insights into biofouling-resistant characteristics of PEGylated PVDF membranes prepared in one step by the polymer blending approach is still unclear. Our previous study showed that a polysulfone surface treated with PEGylated triblock poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (PEO-PPO-PEO) was highly resistant to nonspecific protein adsorption [12].…”
Section: Introductionmentioning
confidence: 99%
“…[58][59][60] In addition, the antifouling properties of some polymer layers come from the mobility of polymers segments that protect the surface from adsorption of protein. It is known that the mobility of chains depends on their chemical structure and the more mobile are chains containing heteroatoms in their internal structure, like polyethers, e.g.…”
Section: Selected Biomedical Applications Of Surfaces Grafted With Pomentioning
confidence: 99%